2009
DOI: 10.1074/jbc.m109.033514
|View full text |Cite
|
Sign up to set email alerts
|

Cell Proliferation and Epidermal Growth Factor Signaling in Non-small Cell Lung Adenocarcinoma Cell Lines Are Dependent on Rin1

Abstract: Rin1 is a Rab5 guanine nucleotide exchange factor that plays an important role in Ras-activated endocytosis and growth factor receptor trafficking in fibroblasts. In this study, we show that Rin1 is expressed at high levels in a large number of non-small cell lung adenocarcinoma cell lines, including Hop62, H650, HCC4006, HCC827, EKVX, HCC2935, and A549. Rin1 depletion from A549 cells resulted in a decrease in cell proliferation that was correlated to a decrease in epidermal growth factor receptor (EGFR) signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…23 The 11q12.2-q13.2 and 19p13.2-p13.11 segments contain several cancer-associated genes such as RIN1, FOSL1, and VEGFB (11q12.2-q13.2) and JUNB and JUND (19p13.2-p13.11) that are duplicated/rearranged and/or overexpressed in various forms of epithelial cancers. [30][31][32] Whether the 11q and 19p gains in mucoepidermoid carcinoma target any of these genes remains, however, to be shown. The most frequent copy number alterations detected in the 28 mucoepidermoid carcinomas were losses of 18q12.2-qter, 9p21.3, 6q22.1-q23.1, and 8pter-p12.1, and gains of 8q24.3, 11q12.3-q13.2, 3q26.1-q28, 19p13.2-p13.11, and 8q11.1-q12.2.…”
Section: Discussionmentioning
confidence: 99%
“…23 The 11q12.2-q13.2 and 19p13.2-p13.11 segments contain several cancer-associated genes such as RIN1, FOSL1, and VEGFB (11q12.2-q13.2) and JUNB and JUND (19p13.2-p13.11) that are duplicated/rearranged and/or overexpressed in various forms of epithelial cancers. [30][31][32] Whether the 11q and 19p gains in mucoepidermoid carcinoma target any of these genes remains, however, to be shown. The most frequent copy number alterations detected in the 28 mucoepidermoid carcinomas were losses of 18q12.2-qter, 9p21.3, 6q22.1-q23.1, and 8pter-p12.1, and gains of 8q24.3, 11q12.3-q13.2, 3q26.1-q28, 19p13.2-p13.11, and 8q11.1-q12.2.…”
Section: Discussionmentioning
confidence: 99%
“…In colorectal tumors, Rin1 expression correlated not only with poor prognosis but also with venous invasion (Senda et al 2007). Congruent with growth-factor-driven invasiveness and metastasis, studies performed on lung cancer cell lines suggested that Rin1 regulates cell proliferation through EGFR (Tomshine et al 2009). These observations suggest that the interactions between Rin1 and Abl are favored in tumors more so than the alternative actions of Rin1 on Rab5 and Raf.…”
Section: Endocytosis and Cancermentioning
confidence: 99%
“…The present study investigated the association between certain factors and the effect of BaP on lung cancer progression. Table I shows the background of the cell lines used in the present study (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). A previous study using CD-1 mice indicated that female mice are more susceptible to the carcinogenic effects of BaP compared with males (29).…”
Section: Discussionmentioning
confidence: 99%
“…Comparison between each TADC-CM and mdDC-CM indicated that HCC2935-TADC-CM had the most marked effect on the proliferation, migration and invasion of cancer cells. The HCC2935 cell line was established from the pleural effusion cells of an adenocarcinoma patient (18)(19)(20)(21)(22). Lung cancer with malignant pleural effusion indicates terminal-stage disease (36).…”
Section: Discussionmentioning
confidence: 99%